Soil microbial communities following bush removal in a Namibian savanna - Buyer, Jeffrey S.; Schmidt-Küntzel, Anne; Nghikembua, Matti; Maul, Jude E.; Marker, Laurie (Soil, 2016)
Savanna ecosystems are subject to desertification and bush encroachment, which reduce the carrying capacity for wildlife and livestock. Bush thinning is a management approach that can, at least temporarily, restore grasslands and raise the grazing value of the land. In this study we examined the soil microbial communities under bush and grass in Namibia. We analyzed the soil through a chronosequence where bush was thinned at 9, 5, or 3 years before sampling. Soil microbial biomass, the biomass of specific taxonomic groups, and overall microbial community structure was determined by phospholipid fatty acid analysis, while the community structure of Bacteria, Archaea, and fungi was determined by multiplex terminal restriction fragment length polymorphism analysis. Soil under bush had higher pH, C, N, and microbial biomass than under grass, and the microbial community structure was also altered under bush compared to grass. A major disturbance to the ecosystem, bush thinning, resulted in an altered microbial community structure compared to control plots, but the magnitude of this perturbation gradually declined with time. Community structure was primarily driven by pH, C, and N, while vegetation type, bush thinning, and time since bush thinning were of secondary importance.